A Review of the Relationship Between Social Media Use and Online Prosocial Behavior Among Adolescents - Lysenstøen, Christoffer; Bøe, Tormod; Hjetland, Gunnhild Johnsen; Skogen, Jens Christoffer (Frontiers in Psychology, 2021)
Social media activity constitutes a large part of adolescents` lives. Even though the behavior on social media is complex, the research on social media have mostly focused on negative effects, bad content and online antisocial behavior. Less research has been conducted on online prosocial behavior and to what extent online prosocial behaviors are widespread is relatively unknown. A review was conducted to investigate to what extent online prosocial behavior is related to social media use among adolescents based on studies published from 2014 up until May 2021. To be included, the studies had to be quantitative, non-experimental, have participants aged 13-18, include measures of social media and online prosocial behavior, and be published in peer-reviewed journals with full text available in English, Swedish, Danish or Norwegian. A search was conducted in databases PsychINFO, Ovid MEDLINE(R), EMBASE, COCHRANE Database of Systematic Reviews, Web of Science, Sociological Abstracts, and Sociological Services Abstracts and Eric. Two studies met the eligibility criteria. Both studies found an association between online prosocial behavior and social media use. Methodological issues, however, identified through a quality assessment using an adapted version of the Newcastle-Ottawa Scale for cross-sectional studies, as well as the small samples in the studies, prevent us from drawing any firm conclusions. Possible reasons for the scarcity of eligible studies and directions for future research are discussed.